Actual and optimal abundance of the main ungulate species in forestry and hunting districts of Ukraine - Ihor Sheihas; Ihor Gulyk (Theriologia Ukrainica)
The article presents the results of a 5-year study (2020–2024) of the state, limits of availability and productivity of the forage base for populations of key species of ungulates, as well as the determination of their optimal abundance (OA) in all five forestry districts of Ukraine. The options for minimum and maximum values of the food base of wild herbivores were fully surveyed and analysed. The following wild game species were subject to a more comprehensive survey: European elk, red deer, European roe deer, and wild boar. Alien species such as sika deer, mouflon, and fallow deer were surveyed to a more limited extent. The limits (OA-min and OA-max) of the acceptable total ungulate abundance depending on the productivity of hunting grounds were determined. Calculations of the allowable population density and the optimal abundance of ungulates depending on the quality score of the grounds were made: from the least suitable to the best. The calculation of the OA for the main species of ungulates in the hunting grounds of the five natural zones gave the following results: 1) in the Polissia zone, OA-min 65.7k thousand ind., average 564.9 thousand ind., actual OA-fact 112.1 thousand ind, OA-fact 42.4 thousand ind.; 2) in the Forest-Steppe zone, OA-min 81.3 thousand ind., OA-max 162.2 thousand ind., OA-fact 42.4 thousand ind.; 3) in the Steppe zone, OA-min (quality score 4.0) 122.9 thousand ind., OA-max (quality score 1.5) 193.5 thousand ind.; OA-fact 34.9 thousand ind.; 4) in the Carpathian zone OA-min (quality score 4.0) 55.5 thousand ind, OA-max (quality score 1.5) 142.3 thousand ind., OA-fact 50.5 thousand ind.; 5) in the Crimean zone, OA-min (quality score 4.0) 45.6 thousand ind. and OA-opt (quality score 1.5) 138.8 thousand ind., OA-fact 7.3 thousand ind. The actual OA increases in the order of Crimea (7.3) → Steppe (34.9) → Forest-Steppe (42.4) → Carpathians (50.5) → Polissia (112.1 thousand individuals), i.e. it changes, albeit gradually, by more than 15 times when moving from southern to northern zones. Within each zone, transitions from a quality score of 4.0 to 1.5 give an increase in OA by 3.5–4.0 times. The possibilities of a significant increase in the optimal number of ungulates in the lands of each of the considered natural zones (forestry and hunting districts) are shown, but only if fundamental changes in the principles of hunting management are provided.